2014
DOI: 10.1002/app.40820
|View full text |Cite
|
Sign up to set email alerts
|

Production of biodegradable polyesters via enzymatic polymerization and solid state finishing

Abstract: The synthesis of aliphatic polyesters (PEs) derived from diols (1,4-butanediol and 1,8-octanediol) and diacids or their derivatives (diethyl succinate, sebacic acid, 1,12-dodecanedioic acid, and 1,14-tetradecanedioic acid) was achieved in order to produce poly(butylene succinate) (PE 4.4), poly(octylene sebacate) (PE 8.10), poly(octylene dodecanate) (PE 8.12), and poly(octylene tetradecanate) (PE 8.14). The herein suggested procedure involved two stages, both sustainable and in accordance with the principles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Similar results were reported by Catalani el al. 24 and Papaspyrides et al 50 on the effect of the chain length of dicarboxylic acids/diacid ethyl esters on enzymatic polymerization. Catalani el al.…”
Section: Calb-catalyzed Synthesis Of Biobased Saturated and Unsaturatmentioning
confidence: 99%
“…Similar results were reported by Catalani el al. 24 and Papaspyrides et al 50 on the effect of the chain length of dicarboxylic acids/diacid ethyl esters on enzymatic polymerization. Catalani el al.…”
Section: Calb-catalyzed Synthesis Of Biobased Saturated and Unsaturatmentioning
confidence: 99%
“…However, higher concentration of enzyme not always results in higher molecular weight as demonstrated by Kanelli et al. [ 93 ] They studied the effect of 10 and 20 wt% of immobilized CALB over the polymerization reaction of 1,8‐octanediol and 1,12‐dodecanedioic acid. Although an improvement in the reaction yield was observed with higher amount of enzyme as catalyst, both reactions produced polymers with M n differing only by about 500 g mol −1 ; M n reached a plateau for the reaction conditions studied despite of the enzyme concentration.…”
Section: Enzymes In Polymer Chemistrymentioning
confidence: 99%
“…In addition, Kanelli et al. [ 93 ] observed an increasing trend in the M n after the enzymatic polymerization for 4 h of 1,8‐octanediol with dicarboxylic acids of C4 and C10 lengths in diphenyl ether. In this particular case, a further increase of the diacid length from C10 to C14 decreased the M n from 8020 to 5360 g mol −1 .…”
Section: Enzymes In Polymer Chemistrymentioning
confidence: 99%
“…21 On the other hand, recent studies suggested a benecial effect of an increase of the diester length on the results of enzymatic polycondensation. 12,32,33 For these reasons we moved to verify the extendibility of the approach to longer diacid esters. The sebacic acid diethyl ester was chosen as the model substrate and its transesterication with DHMF was rst proven at atmospheric pressure in dry THF, as described for diethyl succinate.…”
Section: S6 †)mentioning
confidence: 99%